Gender Based Analysis of Critical Thinking in Multicultural Islamic Education among Science and Technology Students - Wawan Purnama; Rachanda Ambya; Uus Ruswandi; Yulia Kuraesin Ila Rohima; Tatang Muh Nasir (Journal of Education Technology, 2025)
Critical thinking skills, particularly among university students, play a vital role in problem-solving and serve as essential preparation for entering the workforce. However, in practice, many students still struggle to develop critical thinking skills, especially in understanding complex issues they encounter. The purpose of this study is to examine how effectively students can think critically in understanding multicultural education from an Islamic perspective and to analyze variations in opinions based on gender. Using a descriptive quantitative methodology, the study involved 40 students, equally representing male and female participants selected through purposive sampling. Data were collected using a critical thinking assessment rubric covering aspects such as problem understanding, information analysis, argument preparation, evidence evaluation, logical conclusion, self-reflection, and problem-solving. The findings revealed that students generally demonstrated strong critical thinking abilities, with an average score of 478.4 out of 595 (80.4%). However, score distribution varied, with male students showing a more heterogeneous range, while female students exhibited a more homogeneous and balanced pattern. This study provides new insights by integrating gender aspects into the analysis of critical thinking within the framework of Islamic education. The practical implications include recommendations for developing multicultural curricula and learning strategies that are more responsive to gender differences and cultural diversity within Islamic educational settings.